(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Our research of the genus Ceutorhynchus associated with oilseed rape was conducted in northern parts of Serbia (Stari Žednik, Subotica). A specific assemblage of eight weevil species was found. The most numerous were stem weevils Ceutorhynchus napi with 81% of all trapped specimens, followed by C. pallidactylus with 18%. The remaining six weevil specimens were C. obstrictus, C.erysimi, C. minutus, C. picitarsis, C. sulcicollis and C. typhae, comprising 1% of all trapped insects. Stem weevils C. napi and C. pallidactylus began to immigrate into the oilseed rape fields in autumn, as early as November 10 (BBCH 17-18). The maximum flight was recorded at the beginning of oilseed rape stem elongation (BBCH 22-25) on March 23. A new generation of C. pallidactylus emerged from oilseed rape fields in June (BBCH 76-88), while individual specimens occurred during the autumn. The majority of C. napi emerged in March next year, sporadically until May 7. As a consequence of C. napi dominance insecticide treatment should be performed earlier than usual, i.e. when C. pallidactilus is the primary target.